Physicians' and Public Attitudes Toward Euthanasia in People with Advanced Dementia - Brinkman‐Stoppelenburg, Arianne (J Am Geriatr Soc, 2020)
BACKGROUND/OBJECTIVES: To explore the opinion of the Dutch general public and of physicians regarding euthanasia in patients with advanced dementia. DESIGN: A cross‐sectional survey. SETTING: The Netherlands. PARTICIPANTS: Random samples of 1,965 citizens (response = 1,965/2,641 [75%]) and 1,147 physicians (response = 1,147/2,232 [51%]). MEASUREMENTS: The general public was asked to what extent they agreed with the statement “I think that people with dementia should be eligible for euthanasia, even if they no longer understand what is happening (if they have previously asked for it).” Physicians were asked whether they were of the opinion that performing euthanasia is conceivable in patients with advanced dementia, on the basis of a written advance directive, in the absence of severe comorbidities. Multivariable logistic regression was performed to identify factors associated with the acceptance of euthanasia. RESULTS: A total of 60% of the general public agreed that people with advanced dementia should be eligible for euthanasia. Factors associated with a positive attitude toward euthanasia were being female, age between 40 and 69 years, and higher educational level. Considering religion important was associated with lower acceptance. The percentage of physicians who considered it acceptable to perform euthanasia in people with advanced dementia was 24% for general practitioners, 23% for clinical specialists, and 8% for nursing home physicians. Having ever performed euthanasia before was positively associated with physicians considering euthanasia conceivable. Being female, having religious beliefs, and being a nursing home physician were negatively associated with regarding performing euthanasia as conceivable. CONCLUSION: There is a discrepancy between public acceptance of euthanasia in patients with advanced dementia and physicians' conceivability of performing euthanasia in these patients. This discrepancy may cause tensions in daily practice because patients' and families' expectations may not be met. It urges patients, families, and physicians to discuss mutual expectations in these complex situations in a comprehensive and timely manner. J Am Geriatr Soc 68:2319–2328, 2020.